2018
DOI: 10.26452/ijrps.v9i1.1188
|View full text |Cite
|
Sign up to set email alerts
|

Various chemical groups produced by endophytic fungi isolated from the Calotropis procera- A pharmaceutically important xerophytic plant

Abstract: In the present study leaf tissue of host plant Calotropis procera was screened for the presence of endophytic fungi. The crude extract of the isolated endophytic fungi was tested for various chemical groups like alkaloids, flavonoids, diterpenoids and phenols. Our study showed the presence of 25 endophytic fungi isolated from the leaf tissue which constituted15 Hyphomycetes, 3 Ascomycetes, 3 Coelomycetes and 4 sterile forms. The qualitative analysis in all the 25 isolates showed the presence of alkaloid, pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…The identified of many bioactive compounds produced by endophytic fungi that have been isolated from desert plants, medicinal plants or other. Isolation of 25 endophytic fungi from the leaves of the Calotropis procera plant, which is a desert plant, and it was found that these fungi produce a variety of compounds such as terpenoids, phenols, alkaloids, flavonoids [12]. Also isolate 10 endophytic fungi from the Salvadora persica plant producing sixty-two bioactive compounds [13].…”
Section: Resultsmentioning
confidence: 99%
“…The identified of many bioactive compounds produced by endophytic fungi that have been isolated from desert plants, medicinal plants or other. Isolation of 25 endophytic fungi from the leaves of the Calotropis procera plant, which is a desert plant, and it was found that these fungi produce a variety of compounds such as terpenoids, phenols, alkaloids, flavonoids [12]. Also isolate 10 endophytic fungi from the Salvadora persica plant producing sixty-two bioactive compounds [13].…”
Section: Resultsmentioning
confidence: 99%